ПРОТОКОЛ ДВОЦЕНТРОВОГО РАНДОМІЗОВАНОГО КОНТРОЛЬОВАНОГО КЛІНІЧНОГО ДОСЛІДЖЕННЯ З ПОРІВНЯННЯ ЛАПАРОСКОПІЧНОЇ ТА ВІДКРИТОЇ «МІНОРНОЇ» РЕЗЕКЦІЇ У ХВОРИХ УКРАЇНИ НА КОЛОРЕКТАЛЬНИЙ РАК З МЕТАСТАЗАМИ ДО ПЕЧІНКИ - BURLAKA, A.; ZEMSKOV, S.; BEZVERKHNYI, V.; BEZNOSENKO, A. (PH Akademperiodyka, 2025)
Background. World statistics demonstrates that about 15% of liver resections are performed laparoscopically. Nevertheless, in Ukrainian specialized centers, this figure is about 5% or even less. The aim of the forthcoming trial is to determine whether laparoscopic liver resections (LLR) performed in the state Ukrainian specialized centers have better surgical and long-term oncological outcomes compared to an open approach (OLR) with the parallel examination of the surgically induced systemic stress response. Methods. This trial is a national (Ukrainian) multicenter randomized controlled trial, with patients and ward personnel blinded to the treatment approach. Patients will be randomized in a 1:1 ratio to LLR or OLR with REDCap® software. The primary end-point is to compare the time to discharge in the cohorts under study. The goal is to reduce the length of hospital stay in the LLR group at least by 28%. To obtain a power of 80% and an alpha level of 0.05 for a two-sided p-value, a minimum of 126 patients (63 in each group) are to be included. Discussion. Conducting a randomized trial in Ukraine comparing laparoscopic and open minor liver surgery techniques can leverage the country’s diverse patient demographics and healthcare infrastructure. This study will be able to provide crucial insights into the effectiveness, safety, and feasibility of both surgical approaches in a population that may have different disease presentations and healthcare access compared to Western countries. Trial registration and status. The trial was registered in Researchregistry.com (UIN10336) on May 26, 2024, and currently has recruited 38 patients.